Compact photonic crystal integrated circuit for all‐optical logic operation. Issue 4 (1st August 2016) - Xavier, Susan Christina; Carolin, B. Elizebeth; Kabilan, Arunachalam P.; Johnson, William
Abstract : Photonic integrated circuits (PICs) will be pushed to electronic integrated circuits in the forthcoming decade because of its package density, interconnections, improved functionality and cost effectiveness. In this study, the authors propose a new configuration of photonic crystal (PhC) integrated circuits to realise the operation of all‐optical logic AND function that operates at a speed of hundreds of gigabits per second. The integrated circuit comprises of lasers, waveguide couplers, logic gate, amplifier and threshold limiter in a two‐dimensional (2D) silicon PhC platform. The behaviour of the proposed structure is qualitatively analysed by the use of 2D finite‐difference time‐domain method. The results show that the integrated circuit performs the required logic operation. The average area required for the entire device including regenerated circuit is 25 × 10 μm 2 . The overall response time is <2 ps. This device is one of the promising platforms for future optical computers and optical signal processor.